Pengaruh Terapi Zikir dalam Mengontrol Halusinasi Pendengaran di Rumah Sakit Jiwa Daerah (RSJD) Provinsi Jambi - Mentari, Dewi; Yuliana, Yuliana; Makeama, Luri (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effect of dhikr therapy in controlling auditory hallucinations in mental health patients at the Jambi Provincial Mental Hospital. This study used a quasi-experimental research type with a One Group pre-test and post-test design with dhikr therapy intervention. A sample of 10 respondents used a purposive sampling technique method in patients with auditory hallucinations at the Jambi Provincial Mental Hospital. The statistical test used was a paired t-test. The results of the study showed that there was an effect of dhikr therapy in controlling auditory hallucinations at the Jambi Provincial Mental Hospital.